PTH-059 The nutrition team experience in a district general hospital: a 7-year review of the impact on parenteral nutrition. (23rd September 2015) - McCorry, R; Mooney, P D; Coulthurst, P; Earley, T; Shaw, T; Clarkson, Y; Allcock, R; Fleet, R; Longden, C; Barnes, A; Shields, P L
Abstract : Introduction: A multidisciplinary nutrition team was introduced in 2002 after an initial retrospective audit demonstrated a high rate of inappropriate parenteral nutrition (PN) use and associated complications with unregulated use. The team comprises a gastroenterologist, nutrition nurse, dietician, microbiologist, pharmacist and a biochemist. This audit was carried out to assess the role of the nutrition team since its introduction. Methods: All patients accepted for PN between 2002 and 2009 were included in this prospective audit. Patient demographics, indications, duration, complications and outcomes were recorded. Results: 202 patients (107 male, 95 female, mean age 62, range 16–85) received PN, for a total of 4668 PN days. Median duration of PN administration was 9 days (range 1–365). Over the study period the service has expanded, with the number of patients receiving PN increasing from 19 patients in 2002 to 56 patients in 2009. There has been a wide range of indications for PN including high output stomas, fistulae and other complex abdominal conditions. The predominant indication for PN was paralytic ileus (36%). 39 catheter related infections developed in 35 (17%) patients, giving a rate of 0.83 catheter related infection per 100 PN days. This improved from 1.82 in 2002 to 0.69 in 2009 as a result of line management training provided by nutrition nurses. Coagulase negative Staphylococcus was the most frequently cultured organism (35%). Over the same period there were 4 catheter related infections in 19 home PN (HPN) patients managed by the nutrition team. The 4 infections were observed in two patients who were both self administering PN. The rate of infection in the HPN patients was 0.06 per 100 PN days. 70 (35%) patients died while on PN, however no deaths were attributable to PN. A total of 100 (50%) patients returned to enteral feeding. Conclusion: There has been a steady rise in referrals to the nutrition team. There has been more judicious PN use and those with a functioning gastro-intestinal tract are directed towards enteral feeding with bridled naso-gastric or naso-jejunal tubes, also supervised by the nutrition team. The introduction of specialist nutrition nurses has seen an improvement in the rate of catheter related infection. The significantly lower rate of catheter related infection in HPN patients suggests that line management can be improved. Further improvement may be possible with the introduction of a dedicated line management team and ring fenced nutrition beds within the surgical unit.